STIGMA RECEPTIVITY AND POLLEN VIABILITY OF Melaleuca alternifolia - Baskorowati, Liliana (Indonesian Journal of Forestry Research, 2009)
Stigma  receptivity based on seed set and pollen  tubes growth  following controlled pollination of flowers  of different  ages was examined  in Melaleuca alternifolia. The stigma secretion during 10 days after anthesis and pollen viability under three different temperatures and five storage times were also observed. These series of research were undertaken because successful controlled pollination of M. alternifolia depends on the application of viable pollen to the receptive compatible  stigma. The objective of this research was therefore to determine the stigma receptivity and pollen viability of M. alternifolia. Results showed that the stigma receptivity began to develop  on day  one and finished  on day  seven after anthesis,  peak receptivity occurred from day three to day six. The stigma receptivity also coincides with the appearance of secretion in the stigma, occurring  from day three to day seven after anthesis. Therefore,  the time for pollination of M. alternifolia appeared to extend for  approximately 7 days after anthesis. Data for M. alternifolia showed that regardless of storage temperature, pollen  was still  viable  after 26 weeks  of storage;  results also demonstrated  that the lowest temperature  (-18oC) was the best regime for long term storage.